Opini Netizen tentang Iklan Rebranding Sorabel” (Studi Deskriptif pada Netizen Pengikut Kampanye #Cobadulubarubayar) - KN, Jamiati (Telangke:Jurnal Telangke Ilmu Komunikasi, 2023)
Sale Stock, one of the Marketplaces in the field of women's fashion, is rebranding to Sorabel. This rebranding has been carried out since January 14 2019, accompanied by changes in the form of the website and applications for smartphones. With this title, Sorabel guarantees that the quality of each product, service and price can compete with other marketplaces. This startup always innovates in serving its clients. Innovation “Try First Then Pay. This research intends to identify and analyze what audiences think about Sorabel's rebranding ads on Instagram with #hastag#codulubarupaid. A qualitative research approach by outlining the results of questions and answers to campaign followers, directly or indirectly by netizens who participated in the sorabel #codulubarupaid campaign. The type of research used is descriptive, because the researcher will define and explain what the audience views about Sorabel's rebranding advertisement #trydulubarupaid through the campaign. The results of this research prove that netizens are enticed to take part in the #Cobadulubarupaid campaign because the theme used is attractive, Be Fashionable Forever, so that netizens look better and always look fashionable. Most informants recognized Sorabel's rebranding before exploring the #Cobadulubarupaid campaign. However, several informants said that Sorabel was a Salestock even though they had explored the #Cobadulubarupaid campaign. From the results of this research, it can be concluded that the views of netizens regarding their interest in participating in the #Cobadulubarupaid campaign are captivated because the theme carried by Sorabel is interesting and different from other competitors.